Combined impact method in the preparatory period of the annual macrocycle of female volleyball players aged 18-19 years old - Boichuk, R.; Iermakov, S.; Vintoniak, O.; Yermakova, T. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. The work aim is to develop and experimentally test the combined impact method performance in the preparatory period of the annual macrocycle of 18-19 year old volleyball players (girls). Material and Methods. The study involved volleyball players (girls) aged 18-19 years old (n = 24, training experience - 9 years). Volleyball players (girls) were divided into control (n = 12) and experimental (n = 12) groups. Results. The method contributed to a higher rate of growth of most parameters of special readiness among volleyball players (girls) of the experimental group. A significant improvement in special readiness (p <0.05) was revealed for all parameters in both groups. In the experimental group, an improvement (p <0.001) was observed for 8 out of 11 parameters. In the control group, a significant improvement in the results (p <0.001) occurred in 3 cases out of 11. A significant improvement in speed and strength training parameters (p <0.001) was revealed: in 3 out of 4 cases (experimental group); in 1 out of 4 cases (control group). The quality of performance of the game basic techniques improved by: 4-22% (p <0.04-0.001 in experimental group) 4-11% (p <0.05-0.02 in control group). Conclusions. It is advisable to devote more time to the development of more significant motor abilities of volleyball players (girls) (speed, speed and strength, dexterity and coordination). It is advisable to improve endurance in combination with the development of other motor abilities and in the process of technical and tactical improvement. In the physical training of volleyball players (girls), it is advisable to use as many training means as possible, which are similar to the main game techniques according to spatio-temporal and dynamic characteristics. Movements with load contribute to the development of intermuscular coordination and allow to quickly form the correct idea of the trained motor action.